Method of zakat assessment on shares in Malaysia: An overview - Wan Anisah, Endut; Suraya, Ismail; Ahmad, Othman (2015)
The main purpose of this paper is to identify the method of zakat assessment on shares in Malaysia. Shares is a form of wealth currently in Malaysia in which zakat is permissible. The method of zakat assessment on shares is still debated among scholars. The question is, what is the method of shares zakat assessment discussed among scholars? What is the method of zakat assessment on shares practiced in Malaysia? Based on content analysis, various methods of zakat assessment on shares have been identified in Malaysia. This variability is caused by the zakat management authorities including determining the method of zakat assessment which falls under the jurisdiction of the various states in Malaysia.